PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) DENGAN MENGGUNAKAN PETA KONSEP UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X LINTAS MINAT EKONOMI DI SMA NEGERI 02 BATU - Agus Saifuddin; Nasikh Nasikh; Sugeng Hadi Utomo (Universitas Negeri Malang, 2015)
This research was conducted in order to determine that the application of learning models and Explaining Student Facilitator (SFE) is able to enhance the activity and student achievement on economic subjects in class X Cross Economic Interests D SMA 02 Batu. This study used a qualitative research approach, with a type of action research. Data from this study colected through student activity observation sheet, documentation, field notes, test questions in the form of pre-test and post-test.